IMPLEMENTATION OF THE MARKETING ORIENTATION IN POLAND BY LIFE INSURANCE COMPANIES - Beata Nowotarska-Romaniak (Polityki Europejskie, Finanse i Marketing)
Marketing is a tool for expansion and fight for company to achieve a position on the market, which is judged by generally accepted standards such as: sales volume, market share and profit levels. Marketing orientation of life insurance companies as a source of income shows customer needs and preferences, so that targeted offers and marketed insurance services meet the needs and preferences better than those of the competition. The company's marketing orientation is the need to adapt constantly to changing market conditions. The article presents scope of the implementation of the marketing orientation by life insurance companies based on of the survey. The aim of the study was to determine: primary purpose of the operations of life insurance companies, a strategy of action to customers, way to identify customer needs and make employees aware of the way that the company implements marketing orientation activities.